2021
DOI: 10.1038/s41598-021-98916-7
|View full text |Cite
|
Sign up to set email alerts
|

Myricetin ameliorates ox-LDL-induced HUVECs apoptosis and inflammation via lncRNA GAS5 upregulating the expression of miR-29a-3p

Abstract: Oxidized low-density lipoprotein (ox-LDL)-induced endothelial cell dysfunction is a significant event in the progression of atherosclerosis. Even Myricetin (Myr) has been exhibited strong antioxidant potency, the effect on atherosclerosis is still elusive. HUVECs were subjected to ox-LDL, before which cells were preconditioned with Myr. Cell Counting Kit-8 assay, flow cytometry, quantitative real-time polymerase chain reaction and Western blot were carried out to assess the impacts of ox-LDL and Myr on HUVECs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 27 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…It was shown that myricetin can exert a protective effect on LPS-induced early inflammation in cardiomyocytes by inhibiting IL-6 and IL-1β expression through NF-B signaling pathway ( Chen and Fan, 2018 ). Similarly, myricetin also inhibited the apoptosis and inflammatory response of human umbilical vein endothelial cells HUVECs by upregulating the expression of miR-29a-3p ( Bai et al, 2021 ). In general, myricetin can enhance body immunity and inhibit cytokine storms by regulating multiple signaling pathways ( Cheung et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that myricetin can exert a protective effect on LPS-induced early inflammation in cardiomyocytes by inhibiting IL-6 and IL-1β expression through NF-B signaling pathway ( Chen and Fan, 2018 ). Similarly, myricetin also inhibited the apoptosis and inflammatory response of human umbilical vein endothelial cells HUVECs by upregulating the expression of miR-29a-3p ( Bai et al, 2021 ). In general, myricetin can enhance body immunity and inhibit cytokine storms by regulating multiple signaling pathways ( Cheung et al, 2000 ).…”
Section: Discussionmentioning
confidence: 99%
“…Aberrant level of miR-29a has been observed in POF tissues [ 26 ]. miR-29a has been reported to inhibit the apoptosis of various cell types, including cardiomyocytes [ 60 ], vascular endothelial cells [ 61 ], and spermatogenic cells [ 62 ]. In our study, we conducted experiments on the biological effects of human UCMSC-derived exosomes carrying miR-29a and their mechanisms against POI progression.…”
Section: Discussionmentioning
confidence: 99%
“…International Journal of Nanomedicine 2023:18 6758 in mitigating colitis, 40 myocardial ischemia-reperfusion injury, 41 and endothelial dysfunction. 42 Myocardial injury in patients with SAP is infrequent, yet it can result in fatal consequences. Utilizing mesenchymal stem cell-derived extracellular vesicles containing miR-29a-3p exhibits promising therapeutic potential for treating myocardial injury associated with SAP.…”
Section: Dovepressmentioning
confidence: 99%